PERFORMANCE ANALYSIS OF FINANCIAL STATEMENTS IN SEMEN INDONESIA, Tbk - nur hidayah (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2021)
This study aims to determine the financial performance of PT Semen Indonesia, Tbk. This type of research is descriptive qualitative which describes the financial ratios consisting of liquidity ratios, solvency ratios, profitability ratios, and activity ratios. The research data is taken from the financial statements of PT. Semen Indonesia (Persero), Tbk for the last two years (2018-2019). The results showed that the financial performance at PT Semen Indonesia (Persero), Tbk based on the Liquidity Ratio using three formulas, namely Current Ratio, Quick Ratio, and Cash Ratio. The solvency ratio uses two formulas, namely Debt To Asset Ratio and Debt To Equity Ratio. Profitability ratios use three formulas, namely Return On Assets, Return On Equity, and Gross Profit Margin. The activity ratio uses three formulas, namely Total Asset Turnover Ratio, Receivable Turnover Ratio, and Inventory Turnover Ratio.